TINGKAT KESIAPAN KOMPONEN WISATA KREATIF JAYENGAN KAMPOENG PERMATA BERDASARKAN STAKEHOLDER - Suryono, Lintang Praharyaning; Astuti, Winny; Rahayu, Murtanti Jani (Regional Development Information Center, Universitas Sebelas Maret, 2016)
Jayengan Kampoeng Permata is a village ofgem merchant Banjar community which is now being planned to become a creative tourism destination. This study aims to determine how the level of readiness of creative tourism components Jayengan Kampoeng Permata by stakeholders. This study uses a deductive-quantitative method. The sampling technique used purposive sampling with JKP’sstakeholders as the interviewees. JKP’s readiness level was somewhat prepared. Components that contributed the highest value to lowest for readiness of JKP are creative tourism community, infrastructure, attractiveness, external institutions, tourists and internal institutional. The results showed that the readiness of people not guarantee readiness Jayengan Kampoeng Permata as a creative tourism destination, fascination owned Jayengan Kampoeng Permata has not been able to invite tourists, the readiness of JKP’s infrastructure sufficient not been able to attract tourists, internal institutional role in supporting preparedness Jayengan Kampoeng Permata and external institutions as external factors readiness JKP.